(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Squamous cell carcinoma in upper aerodigestive tract is most often caused by smoking. Smokers get laryngeal cancer, while chewers get mouth cancer. With the surge in smokeless tobacco use, it’s important to determine if this differentiation influences clinical and pathological characteristics beyond site distribution. Objective: The purpose of the present study was to assess any relation between tobacco smoking, oral intake of tobacco with betel leaf or tobacco powder and squamous cell carcinoma in upper aero digestive tract. Methodology: This cross-sectional study was conducted in a single Diagnostic center at Dhaka, Bangladesh for a period of one year from July 2022 to June 2023 on patients presented with histopathologically established upper aerodigestive tract malignancies. Patients age, gender and involved site was taken from the patients report. Results: Male were predominant than female. Male to female ratio was 3.3:1. Mean age of the patients was 59.26 ± 12.55 years of the male and 56.11 ± 13.13 years of the female. Cancer was more in female at 5th and 6th decade whereas cancer was found more in male at 6th and 7th decade. Most common location of the lesions was sub-glottis (27.6%) and tongue (20.0%). The most common causes of Upper Aerodigestive Tract cancer were smoking (76.2%) and smokeless tobacco using (54.1%). There was no association between smoke and smokeless tobacco with severity of carcinoma. Maximum cases of carcinoma were grade II but there was no significant difference in grade of carcinoma between tobacco smoker and tobacco non-smoker. There was no significant difference in grade of malignancy between tobacco user and non-user. Conclusion: Smoke and/or smokeless tobacco user have increased risk of development squamous cell carcinoma in upper aerodigestive tract. However, there is no significant difference between incidence and grade of tumor among only smoker, smokeless tobacco user or both. Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):52-56